Relación de la morfología floral con la compatibilidad genética en 13 clones élites de cacao (Theobroma cacao L.) - Segovia Montesdeoca, Verónica del Cisne (2017)
The research project was carried out in the experimental farm "La Represa", owned by Quevedo State Technical University (UTEQ), located in Recinto Faita, kilometer 7.5 of Vía San Carlos, in Quevedo, in the province of Los Ríos. The objective was to evaluate the relationship between floral morphology and genetic compatibility in 13 elite cocoa clones (Theobroma cacao L.). An incomplete diallel design was used. To evaluate the auto compatibility and cross-compatibility of the clones. For the study of floral biology, a Completely Random Design (DCA) was used with three observations; The variables evaluated were: peduncle length (LP), sepals length (LS), septal width (AS), petal length (LPE), petal width (AP), staminoid length (LE), pistil length (LPI) and flower weight (PF); The site of incompatibility was also studied. The analysis of the variance was used for the statistical analysis of the data and for comparisons of means the Tukey test was used at 5% probability. As conclusion, it was obtained that the clone that presented the greater percentage of auto compatibility was the T12. DICYT 214, National type, while for cross-compatibility the DICYT-29 X DICYT-67 crossing was highlighted. Also, the compatibility was related to the morphological variables of the broad flower of petal and pistil length, which allows to suspect that those clones that present these structures of greater size facilitate their pollination. It was also confirmed that the incompatibility in cocoa (Theobroma cacao L) is of sporophytic type when observing pistils of flowers pollinated manually but not fertilized, since the pollen does not develop the pollen tube to enter the ovary